Non-Arrhenian Temperature-Dependent Viscosity of Alkali(ne) Carbonate Melts at Mantle Pressures - Ritter, Xenia; Guillot, Bertrand; Sator, Nicolas; Desmaele, Elsa; Massuyeau, Malcolm; Sanchez-Valle, Carmen (Frontiers in Earth Science, 2021)
The viscosity of carbonate melts is a fundamental parameter to constrain their migration and ascent rates through the mantle and ultimately, their role as carbon conveyors within the deep carbon cycle. Yet, data on the viscosity of carbonate melts have remained scarce due to experimental limitations and the lack of appropriate theoretical descriptions for molten carbonates. Here, we report the viscosity of K2Mg(CO3)2 and K2Ca(CO3)2 melts up to 13 GPa and 2000 K by means of classical molecular dynamics (MD) simulations using optimized force fields and provide first evidence for non-Arrhenian temperature-dependent viscosity of molten carbonates at mantle pressures. The viscosity of K2Mg(CO3)2 and K2Ca(CO3)2 melts ranges respectively between 0.0056 – 0.0875 Pa.s and 0.0046 – 0.0650 Pa.s in the investigated pressure-temperature interval. Alkali(ne) carbonate melts, i.e. mixed alkali and alkaline earth carbonate melts -K2Mg(CO3)2 and K2Ca(CO3)2- display higher viscosity than alkaline earth carbonate melts -CaCO3 and MgCO3- at similar conditions, possibly reflecting the change in charge distribution upon addition of potassium. The non-Arrhenian temperature-dependence of the viscosity is accurately described by the Vogel-Fulcher-Tammann (VFT) model with activation energies Ea for viscous flow that decrease with temperature at all investigated pressures, e.g. from 100 kJ/mol to 30 kJ/mol between 1300 and 2000 K at 3 GPa. Pressure is found to have a much more moderate effect on the viscosity of alkali(ne) carbonate melts, with activation volumes Va that decrease from 4.5 to 1.9 cm3/mol between 1300 and 2000 K. The non-Arrhenian temperature-viscosity relationship reported here could be exhibited by other carbonate melt compositions as observed for a broad range of silicate melt compositions and it should be thus considered when modeling the mobility of carbonate melts in the upper mantle.